Contributions on the regionalization process in two regions in the Southeast of Brazil - Liza Yurie Teruya Uchimura; Maria Paula Ferreira; Miriam Regina Souza; Ana Luiza d'Ávila Viana
Abstract Objectives: to analyze the contributions of regionalization in North-Barretos and South-Barretos regions, focusing on political, structural and organizational changes. Methods: mixed sequential explanatory methods using records analysis from the Comissão Intergestores Regional (CIR) (Regional Inter-managers Commission (CIR), interviews with questionnaire and guides along with 42 key agents (managers and providers of services) conducted in August 2015. The descriptive statistical results were presented with mean scores for each of the question in the questionnaire. The analysis of the thematic content was performed by using the Atlas-ti software and categories of the mixed themes were generated representing the following dimensions: policy, structure and organization. Results: the study identified that the Estrutura Regional da Secretaria Estadual de Saúde (Regional Structure of the State Health Department) is the most important institution in health policy decisions. Several contributions can be identified in the process of regionalization, mainly in the organizational aspect of the health system. The records demonstrated the frequent presence of themes related to networks, regulation and financing and the definition of flow of patients. Conclusions: regionalization in the North-Barretos and South-Barretos regions have contributed for a better organization in health actions and services. The intergovernmental forums do not work with coordination and they are not a collaborative place to negotiate health issues in these regions in São Paulo State